Emergência climática: resposta a eventos extremos e adaptação para a gestão municipal - Dalla Valle, Ana Carolina (2024)
The planet's climate is influenced by a complex interplay of processes that shape the global climate system and are the subject of intense scientific research. Climate science, whose roots date back to the 19th century, identifies global warming as a central factor in today's profound climate changes, resulting in imbalances that are, to some extent, irreversible. Therefore, a new and urgent field for multisectoral and multilevel public policies is emerging, which deals with adaptation to the new climate reality to which socio-ecological systems are exposed. The relevance of researching and discussing disaster risk mitigation and adaptation to climate change scenarios at the municipal level is highlighted, given that the field of climate issues at the local level still needs to be studied. This study, divided into two articles, seeks to relate the difficulties encountered by public managers and reported by researchers in implementing a local climate political agenda with the challenges faced by a specific and fundamental sector in this scenario, Civil Defense. Thus, a systematic review of publications addressing local policies and initiatives for emergency response and adaptation to climate change conducted by municipal administrations in Brazilian territory is presented. The analysis of the challenges reported in these experiences led to the following categories: problems related to i) institutional arrangement; ii) articulation of knowledge; iii) technical or operational capacity; iv) credibility of public management; v) political culture; vi) sociopolitical history; vii) perception and beliefs about MC; viii) incorporation of the MC agenda into the local agenda; ix) integration between institutions; x) integration of interested parties; xi) planning; xii) execution; xiii) financial resources; xiv) human resources. In the second part, this work analyzes the institutional capacity of civil defenses in municipalities in Paraná to face disasters. Primary data were collected from Civil Defense coordinators from ten municipalities in the western mesoregion of Paraná. The results indicate that the biggest challenges are the physical-financial structure (lack of space and own budget); career structuring and lack of exclusive dedication from teams; and difficulties in preventive work with the population. It was found that municipalities address disaster risk management marginally in their legislation despite having master plans and contingency plans. Considering the climate context, there is an urgent need for greater appreciation of local Civil Defense, providing it with the capacity and autonomy to carry out adequate prevention, mitigation, preparation, response and disaster recovery. Furthermore, it was found that national development policies, food security, water security, among other cross-cutting policies, are fundamental for implementing local actions to adapt and confront extreme events.